Extinction and backscatter measurements of Antarctic PSC's, 1987: Implications for particle and vapor removal - Kelly, K. K.; Trepte, C. R.; Fahey, D. W.; Jones, R. L.; Pueschel, R. F.; Browell, Edward V.; Poole, L. R.; Ferry, G. V.; Mccormick, M. Patrick (1988)
The temperature dependence is examined of optical properties measured in the Antarctic during 1987 at the 70 mb level (near 18 km), a level chosen to correlate the results with in situ measurements made from the NASA-Ames ER-2 aircraft during the 1987 Airborne Antarctic Ozone Experiment (AAOE). The data set consists of extinction measurements by Sam 2 inside the Antarctic polar vortex from May to October 1987; and backscatter measurements by the UV-DIAL (Ultraviolet Differential Absorption Lidar) system aboard the Ames DC-8 aircraft during selected AAOE flights. Observed trends are compared with results from a revised version of Pole and McCormick's model to classify the PSC observations by Type (1 or 2) and infer the temporal behavior of the ambient aerosol and ambient vapor mixing ratios. The sample figures show monthly ensembles of the 70-mb Sam 2 extinction ratio (the ratio of aerosol or PSC extinction to molecule extinction) as a function of NMC temperature at the beginning (June) and (October) of the 1987 Antarctic winter. Both ensembles show two rather distinct clusters of points: one oriented in the near vertical direction which depicts the change with temperature of the ambient aerosol extinction ratio; and a second cluster oriented in the near horizontal direction whose position on the vertical scale marks a change in particle phase (i.e., PSC formation) and whose length (the extinction enhancement related to that of the ambient aerosol) is an indicator of PSC type.